Penyajian Karya Surupan 62 Sebagai Alternatif Surupan Dalam Memperkaya Model Pertunjukan Tembang Sunda Cianjuran - Nurzaini, Mayang Amalia; Wahyudin, Pepep Didin (LP2M ISBI Bandung, 2023)
The presentation of this karawitan project is based on a practiced led research approach which is carried out through practical studies of the Final Project with Vocal of Tembang Sunda Cianjurans majors. This performance focuses on the use of surupan 62 in Haleuang Rasaning Tembang project. This work is based on anxiety about the phenomenon of standardization of surupan 60 which has become a habit in society, thereby reducing the existence of others surupan. Therefore, the author brings back surupan 62 as an alternative of surupan in enriching the Tembang Sunda Cianjuran performance model, especially at ISBI Bandung. To achieve this goal, the practical method of presenting this work is carried out in three stages, are: exploration, evaluation and composition. The result of this creation process is the Tembang Sunda Cianjuran performance which was presented at the Final Project Recital of the Karawitan Study Program, Faculty of Performing Arts, ISBI Bandung, in a virtual performance.